Outcomes of usage of polypropylene mesh in TAPP hernia repair - Kumar, Amit; Malik, Adeel Ahmed; singh, Gurbir; Bhat, Agnishikha (International Journal of Research in Medical Sciences, 2023)
Background: Repair of hernia has seen a paradigm shift from open technique to laparoscopic technique. Laparoscopic transabdominal preperitoneal mesh hernioplasty is the latest technique with several advantages over open repair. Polypropylene (PP) mesh is the most frequently preferred product, as are easily and cheaply available, provide enough strength for the technique with good biocompatibility and less tissue reaction. Objective was to study the outcome of usage of polypropylene mesh in TAPP hernia repair. Methods: It was a prospective study on patients with diagnosis of inguinal hernia and underwent TAPP hernia repair with polypropylene mesh. Results: Total of 60 patients were included. Majority of the patients (18; 30%) were in age groups of 46-55 years and 56-65 years. 67% cases of inguinal hernia were of indirect type, 30% direct type and 3% both direct and indirect. Right-sided inguinal hernia (57%) was more frequent, followed by left sided (23%) and bilateral (20%). Average time taken was 72 to 98 minutes with a mean of 81.33 minutes in the surgery for unilateral repair and 90 to 103 minutes with a mean of 97.66 minutes for bilateral repair. 40 (67%) patients returned to work within 2 weeks of surgery. Conclusions: Inguinal hernia repair is a common surgical procedure performed on daily basis around the world. Delay in treatment can lead to complications. Laparoscopic approach has shown clear advantages regarding less postoperative pain, numbness, fast return to normal activities and decrease in the incidence of wound infection and hematoma. Polypropylene has proven physical, chemical and biological properties and is currently the most widely used allograft in laparoscopic inguinal hernias.